The Uṣūl al-Fiqh Approach on the Understanding of Islamic Law in Contemporary Era: Source and Contextualization - Mudawam, Syafaul (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2021)
Abstract: This article aims to analyze an understanding of Islamic legal theories (uṣūl al-fiqh), referred to as a source and logical framework of how to answer legal problems of humankind’s response in the contemporary era. The paper employed library research to deal with Islamic principles as primary data sources. Findings that the development of uṣūl al-fiqh debate should be involved primary sources of the Islamic law, both independent sources (the Qur’an and sunnah) and dependent sources (ijmā‘, qiyās, istihsan, istiṣlah, and others). In order to answer the contemporary problems, the development of the uṣūl al-fiqh method should be evidenced by the primary objectives of Islamic law (maqāṣid al-syarī‘ah), namely, creating the public interest (maṣlaḥah) for the humanity. However, the contextualization of uṣūl al-fiqh is used by sorting out distinguishing primary sources (authentic) and derivatives sources. Such the proofs are understood to analyze for further discussion on deductive (istidlāl al-istinbāṭī) or inductive reasoning (istidlāl al-istiqrā’ī). Indeed, jurists should be carried on emphasizing the objectives and the wisdom of Islamic law (maqāṣid wa ḥikmah al-syarī‘ah) as their analysis.Abstrak: Artikel ini bertujuan untuk menganalisis sumber dan logika operasional usul fikih dalam menjawab persoalan hukum dan kemanusiaan di era kontemporer. Tulisan ini merupakan penelitian kepustakaan dengan menjadikan kitab-kitab usul fikih sebagai sumber primer. Artikel ini menemukan bahwa pengembangan kajian usul fikih harus didasarkan pada sumber utamanya dalam hukum Islam, baik sumber-sumber independen (Al-Qur’an dan hadis) maupun sumber-sumber dependen (ijmā‘, qiyās, istihsan, istiṣlah, dan sebagainya). Dalam rangka menjawab problematika kontemporer, pengembangan metodologi ushul fikih harus didasarkan pada tujuan utama syari’ah (maqāṣid al-syarī‘ah), yakni menciptakan kemaslahatan bagi umat manusia. Sementara itu, kontekstualisasi usul fikih dapat dilakukan dengan memilah dan membedakan sumber primer (autentik) dan sumber turunan (derivatif). Dalil-dalil tersebut kemudian dipahami dan dianalisis lebih lanjut melalui penalaran deduktif (istidlāl al-istinbātī) ataupun penalaran induktif (istidlāl al-istiqrā’ī). Pada pelaksanaan analisisnya, para ahli hukum Islam perlu memperhatikan dan menekankan pada aspek tujuan dan hikmah dari disyariatkannya hukum Islam (maqāṣid wa ḥikmah al-syarī‘ah).